UPAYA PENGUMPULAN PAJAK (TAX EFFORT) SEBELUM DAN SAAT PANDEMI COVID-19 DI INDONESIA - Ade Nurul Aida (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
This study analyzes the condition of tax efforts in Indonesia before and during the Covid-19 pandemic in Indonesia. The data used is within a period of 4 years, namely before and during the Covid-19 pandemic from 2018 to 2021. The data analysis technique uses the paired sample test analysis tool T-Test or Wilcoxon Non-Parametric Test because this research was conducted by comparing samples research on tax efforts before and during Covid-19. The empirical test results show that there is no significant difference between the tax effort before the pandemic and during the pandemic. Even though the economic condition is still vulnerable and not yet fully stable, the government still must increase its tax efforts appropriately. Low tax efforts can of course have implications for state revenue (especially from taxes) in financing regional development itself.